Optimal Monetary Policy in a Small Open Economy Under Segmented Asset Markets and Sticky Prices - Medina Guzman, Juan Pablo (IMF Working Papers; Working Paper ;, 2007)
This paper studies optimal monetary policy in a two-sector small open economy model under segmented asset markets and sticky prices. We solve the Ramsey problem under full commitment, and characterize the optimal monetary policy in a calibrated version of the model. The findings of the paper are threefold. First, the Ramsey solution mimics the allocations under flexible prices. Second, under the optimal policy the volatility of non-tradable inflation is close to zero. Third, stabilizing nontradable inflation is optimal regardless of the financial structure of the small open economy. Even for a moderate degree of price stickiness, implementing a monetary policy that mitigates asset market segmentation is highly distortionary. This last result suggests that policymakers should resort to other policy instruments in order to correct financial imperfections.